Aryl hydrocarbon receptor deficiency enhances astrocyte sensitivity to LPS-induced inflammation - Ojo, Emmanuel; Tischkau, Shelley A. (Frontiers in Cellular Neuroscience, 2025)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor linked to the control of immunological responses. Although AhR has been investigated in relation to lipopolysaccharide (LPS) peripheral inflammation, its role in LPS-induced, astrocyte-mediated inflammation in vivo is unknown. This study explores the effect of AhR deletion on astrocyte reactivity and neuroinflammation responses to lipopolysaccharide (LPS). The results show that AhR loss aggravates LPS-induced inflammatory responses using a AhR germline knockout (AhRKO) mouse by increasing pro-inflammatory cytokines levels (TNF-α, IL-1β) and inducible nitric oxide synthase (iNOS) in both primary astrocyte cultures and the mouse hippocampus. Morphologically, astrocytes and microglia from AhRKO mice show increased soma size following LPS injection, suggesting increased glial activation. In addition, AhRKO mice displayed more severe weight loss and locomotor impairment behaviorally following a single systemic LPS injection. Elevated nuclear translocation of NF-κB p65 in AhR-deficient astrocytes provides a potential mechanism for elevated pro-inflammatory signaling. These results emphasize an immunomodulatory role for AhR in reducing astrocyte-driven inflammation and identify AhR as possible therapeutic target for neurodegenerative illnesses linked with neuroinflammatory responses.